DECISION IN PURCHASING USED IMPORT CLOTHES IN SURABAYA - Arwita Dwi Andriani; Christina Menuk Sri Handayani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The trend of fashion business development in Surabaya is growing rapidly, not only in new fashion, but also imported secondhand fashion. Although there are still different views on imported used clothes due to health and hygiene factors, there are still people in Surabaya who make use of imported clothes to fulfill their primary needs. The expected goal of this research is to determine the decision to use imported used clothing in Surabaya. Consumers who buy imported used clothes in Surabaya will act as the study population, with an infinite population type and the sample taken from 105 people. The data were collected using a questionnaire which was then tested for validity and reliability. Before testing the hypothesis, a classical assumption test and regression analysis is carried out first. The results show that the decision to use imported used clothing in Surabaya is influenced by lifestyle, product quality and price.